2009
DOI: 10.1007/s00436-009-1555-1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo antifilarial potential of marine sponge, Haliclona exigua (Kirkpatrick), against human lymphatic filarial parasite Brugia malayi

Abstract: The present study reports on the antifilarial activity of a marine sponge Haliclona exigua (phylum Porifera). The crude methanol extract and n-butanol-soluble fraction killed adult Brugia malayi at 31.25-microg/ml concentration (both in motility and 3-(4,5 dimethylthiazol-2-yl)-2,5 diphenyl tetrazolium bromide assay) while the chloroform fraction was lethal at a lower concentration of 15.6 microg/ml. The activity could be located in a single molecule araguspongin C which brought about mortality of worm at 15.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Chemical analyses of the extract revealed that it contained a mixture of four alkaloids ( Figure 1) namely mimosamycin, xestospongin-C, xestospongin-D and araguspongin-C together with few minor compounds [13]. This observation was found to be in resonance with Lakshmi et al [22], on anti-ilarial activity of another species, H. exigua against lymphatic B. malayi. In vitro and in vivo study showed that 31.25 μg/ml concentrations of the crude alcoholic extract soluble fractions were able to kill the adult worms.…”
Section: Haliclona Oculata (Family: Chalinidae): the Demospongie (Halsupporting
confidence: 70%
“…Chemical analyses of the extract revealed that it contained a mixture of four alkaloids ( Figure 1) namely mimosamycin, xestospongin-C, xestospongin-D and araguspongin-C together with few minor compounds [13]. This observation was found to be in resonance with Lakshmi et al [22], on anti-ilarial activity of another species, H. exigua against lymphatic B. malayi. In vitro and in vivo study showed that 31.25 μg/ml concentrations of the crude alcoholic extract soluble fractions were able to kill the adult worms.…”
Section: Haliclona Oculata (Family: Chalinidae): the Demospongie (Halsupporting
confidence: 70%
“…The sponge genus Haliclona is known for its high chemical various secondary metabolites with interesting biological activities (Faulkner 2002) including the antifungal (Barrett et al 1996; Clark et al 2001; El-Wahidi et al 2013), antileishmanial (Dube et al 2007), antioxidant (Regoli et al 2004), cytotoxic (Fusetani et al 1989) and other activities (Lakshmi et al 2009; Randazzo et al 2001). …”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, peritoneal fluid was examined on day 50 during animal autopsy which revealed 60-70% decrease in microfilarial density in the fluid as also similar degree of reduced motility. DEC was used as standard filaricidal drug in vivo as it is a strong microfilaricidal in B. malayi/ Mastomys model, imparting partial adulticidal and embryostatic action (Singh et al 1997) which Ivermectin possesses in vitro microfilaricidal (personal observation) and macrofilaricidal (Lakshmi et al 2009) action on B. malayi, and therefore was selected as a standard drug in in vitro screen. It is well known that DEC is ineffective in vitro (Misra-Bhattacharya et al 2004); however, it was included as a standard drug along with ivermectin in vitro for comparison.…”
Section: Discussionmentioning
confidence: 99%